Management Of T'alim Muhadatsah Activities In Improving Arabic And English Ability For Students Gontor Campus 7: Using The Management Model Of George R, Terry - Aji Putra, Ayang; Patimah, Hj. Siti (Riviera Publishing, 2023)
This research aims to analyze and then explain the management of Ta'lim Muhadatsah activities at Pondok Modern Darussalam Gontor Campus 7, one of the activities aimed at improving the student's ability to speak Arabic and English. The management applied to this activity is POAC (planning, organizing, actuating, controlling). The method used in this research is qualitative, which is conducted by observations, interviews, and reviewing program implementation documents. Sources of information and data were obtained through interviews with ta'lim Muhadatsah supervisors, activity supervisors, and students. The research results show that ta'lim Muhadatsah activities increase the students' skills in speaking Arabic and English, the official Language at Pondok Modern Darussalam Gontor, with the method applied, namely ilqoiyyah method.